Issues in Managing and Sequencing Financial Sector Reforms Lessons From Experiences in Five Developing Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1992)
A review of the experience of five developing countries in reforming their financial systems illustrates the benefits and risks, and provides lessons on the factors which contribute to successful financial sector reforms. Financial sector reforms need to be supported by active monetary policy, and the adoption of new monetary control procedures early in the reform program; reforms should be sequenced consistently with the broader program of macroeconomic adjustment. The pace of liberalization of interest rates and credit should also take account of the solvency of financial and nonfinancial firms. A minimal system of prudential regulation is an essential element of successful financial sector reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet